Partnerships and collaborations in public library communities resources and solutions - Ellis, Karen, 1961-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book shows how partnerships can be cultivated through projects, programming, funding, and extending the library's presence through unique avenues, offering librarians a better understanding of what might be possible for their situational requirements and limitations"--Provided by publisher.
Neighborhood Resource Center : the library partnership / Sol M. Hirsch, Alachua County (Florida) Library District, USA -- Waking up the neighborhood : partnerships with local businesses and art communities / Catherine Hakala-Ausperk, Northeast Ohio Regional Library System, Warren, OH, USA -- El Dorado County libraries in collaboration with First 5 of El Dorado Children and Families Commission and partnering agencies / Carolyn Brooks, El Dorado Hills Branch Library, El Dorado County, CA, USA -- In quest of academic achievement : a public library's partnerships in Onitsha, Anambra State, South East Nigeria / Nkem Ekene Osuigwe, Onitsha Public Library, Anambra, Nigeria -- Lights, camera, library : building community through world class film / Barbara Brattin, Wilkinson Public Library, Telluride, CO, USA -- A new evolution in science collaboration / Erica Segraves, Mamie Doud Eisenhower Public Library, Broomfield, CO, USA -- Cross-generational learning case study : a working partnership between Malahide Library and Malahide (Post-Primary) Community School / Susan Lovatt, Malahide Library, Fingal County Libraries, Ireland -- Partnering to promote financial literacy : the Orange County Library System experience / Paolo Melillo, Orange County Library System, Orlando, FL, USA -- The Hampstead Carbon Challenge / Peggy Thrasher, Dover Public Library, Dover, NH, USA -- Second chance / Kathleen Houlihan, Austin Public Library, Austin, TX, USA -- A rite of passage : New York Public Library Passages Academy / Lindsy D. Serrano, New York Public Library, NY, USA -- Bridging the divide / Hillary Dodge and Erica Rose, Clearview Library District, Colorado, USA -- A furry partnership / Mary L. Hall, Bedford Public Library, Bedford, IN, USA -- A tale of two schools / Karen Ellis, Taylor Public Library, Taylor, TX, USA.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed January 23, 2012).
Keywords: Libraries and community -- Case studies; Adult literacy programs; Business-library partnerships; Collaboration; Community awareness; Community outreach; Educational programming; Employment workshops; Funding; Libraries and communities; Library management; Partnerships; Electronic books